Changes in commuting behaviours in response to the COVID-19 pandemic in the UK. (March 2022) - Harrington, Deirdre M.; Hadjiconstantinou, Michelle
Abstract: Background: The UK Government restrictions on non-essential work in response to the coronavirus disease 2019 (COVID-19) pandemic forced millions of working aged-adults into an unplanned lifestyle change. We present data on changes in commuting behaviour in response to COVID-19 and describe the facilitators and barriers to switching commuting behaviours, with a specific focus on cycling and walking. Methods: An online survey queried individuals' transport mode to/from work before and when becoming aware of COVID-19, when restrictions were in place and the transport mode they may use once restrictions are lifted. Free-form text responses were collected on why they may switch to a sustainable commute mode in the future and what would help/allow them to achieve this. Quantitative and qualitative data on those who commuted by car (single occupant) and public transport (bus/rail/park & ride) were analysed and presented separately. Results: Overall, 725 car and public transport commuters responded; 72.4% were car commuters and 27.6% were public transport commuters before COVID-19. Of the car commuters, 81.9% may continue travelling by car once restrictions are lifted while 3.6% and 6.5% might change to walking and cycling, respectively. Of the public transport commuters, 49.0% might switch modes. From the free-form text responses three themes were identified: (a) perceived behavioural control towards cycling and walking (infrastructure and safety of roads, distance, weather) (b) key motivators to encourage a switch to cycling and walking (provision to support cycling, personal and environmental benefits); (c) the demands of current lifestyle (job requirements, family and lifestyle commitments). Conclusion: These UK data show how the COVID-19 pandemic has been an "external shock" causing some individuals to reassess their commuting mode. This provides an opportunity for theory-based behaviour change interventions tackling motivations, barriers and beliefs towards changing commute mode. Highlights: Some car and public transport commuters in the UK are considering a switch of transport mode once COVID-19 restrictions lift. Positively, some will switch to cycling or walking but some bus/rail users will switch to a car for safety reasons. Barriers and motivators have a role for car and public transport commuters when thinking about changing individual commuting mode. The COVID-19 pandemic provides an opportunity for theory-based transport interventions and actions at individual, social and micro-physical environment levels.